EFFECT OF COMPENSATION WORK ENVIRONMENT AND LEADERSHIP STYLE ON EMPLOYEE SATISFACTION AT DIGIBANK BY DBS INDONESIA (STUDY ON DIGIBANK EMPLOYEES BY DBS) - Faisi Faisi; Kasmir Kasmir (Dinasti Publisher, 2021)
This study aims to partially analyze the influence of the work environment on the job satisfaction of Digibank by DBS Indonesia employees, to partially analyze the effect of compensation on employee satisfaction of Digibank by DBS Indonesia, to partially analyze the influence of leadership styles on the job satisfaction of Digibank by DBS Indonesia employees, to analyze the simultaneous influence between the work environment, compensation and leadership style on the job satisfaction of Digibank employees by DBS Indonesia. The method used in this study uses multiple linear regression analysis, the sample in this study is employees in the digibank section of DBS Bank Indonesia as many as 50 employees who will be used as respondents to fill out questionnaires. The results stated that the work environment has a partially positive and significant effect on employee job satisfaction. Compensation has a partially positive and significant effect on employee job satisfaction. The leadership style partially positively and significantly affects employee job satisfaction. Work environment, compensation and leadership style simultaneously affect employee job satisfaction.